The broken years Russia's disabled war veterans, 1904-1921 - Sumpf, Alexandre 1977- (Studies in the social and cultural history of modern warfare, 2022)
An overwhelming loss -- The right to health -- A social status renegotiated by the war -- Discriminatory social welfare -- An ephemeral political spring -- The devaluation of war experience.